46‐4: High Frame Rate Scanning Backlight System For Gaming PC Display with IGZO‐TFT Technology. Issue 1 (28th June 2021) - Kobayashi, Masamitsu; Miura, Takafumi; Yamaguchi, Noriaki; Miyata, Hidekazu; Yashiki, Masafumi; Masuda, Junichi; Takase, Kenji; Hara, Yoshihito; Kikuchi, Tetsuo; Imai, Hajime
Abstract : The rapid expansion of the gaming PC market in recent years has increased the demand for high frame rate display modules. Especially for laptops, the demand for thinner profiles and narrower borders also continues to be strong. We have developed an LCD module with a combination of a high frame rate LC panel based on IGZO‐TFT technology and a scanning backlight that enables high moving picture quality in a thin profile with narrow borders on three sides. The scanning backlight has fewer segmented areas. Nevertheless, our LCD achieves higher moving picture quality by using a fast response LC.